Diagnostic and mortality outcomes in a cohort of adult meningitis suspects in KwaZulu-Natal. Issue 1 (2nd January 2018) - Nonkala, Onke; Aldous, Colleen; Wilson, Douglas
Abstract: Background: The clinical value of lumbar puncture (LP) in settings with a high human immunodeficiency virus (HIV) prevalence has not been well defined. Methods: We performed a retrospective chart review in 394 adults undergoing LP at a single regional level public-sector hospital in KwaZulu-Natal, South Africa. Results: The median age of all the participants was 32.8 years (interquartile range 26.7; 41.2). Two hundred and fifty-five participants (64.7%) had an abnormal cerebrospinal fluid (CSF) analysis; 202 (79.5%) of whom were HIV seropositive. Sixty-four (25.1%) were diagnosed with tuberculosis meningitis and 62 (24.3%) tested positive for cryptococcal antigen. Thirty-three specimens grew Cryptococcus neoformans (32 tested antigen positive) and Streptococcus pneumonia was isolated in three specimens (0.8%). An abnormal CSF result was associated with increased risk of inpatient death (OR 3.8 [95% CI 1.7; 9.6]; p -value = 0.0004) Conclusions: CSF abnormalities were common in this cohort of adults with suspected meningitis in KwaZulu-Natal, and were associated with increased odds of mortality in hospitalised participants.